Low Expression of 14-3-3beta Is Associated With Adverse Survival of Diffuse Large B-Cell Lymphoma Patients - Li, Chaoping; Li, Zhaoming; Zhang, Mingzhi (Frontiers in Medicine, 2019)
Diffuse large B-cell lymphoma (DLBCL), the most common type of non-Hodgkin's lymphoma in the world, is highly heterogeneous. Although current therapies have improved the clinical outcome, 30–40% of the patients are still not cured. Thus, novel treatment options such as targeted therapy is urgently needed. Accumulating evidence suggests that 14-3-3beta protein plays an important role in tumorigenesis and tumor progression. However, the specific roles of 14-3-3beta in DLBCL are still poorly understood. In this study, we retrospectively analyzed 120 archived wax blocks obtained from patients with DLBCL (n=70) and non-neoplastic lymph nodes (n=50). Immunohistochemical staining showed that 14-3-3beta gene expression was significantly decreased in DLBCL tissues (P < 0.001) compared to that in non-neoplastic lymph nodes. Low 14-3-3beta expression was significantly correlated with extra-nodal status (P=0.026), serum LDH level (P=0.023) and adverse survival of DLBCL patients. In survival analyses, low 14-3-3beta expression was significantly associated with adverse overall survival of the DLBCL patients (P=0.003). Using the Kaplan-Meier analysis module of the R2 microarray analysis and visualization platform (http://r2.amc.nl), we also confirmed that low expression of 14-3-3beta gene had inferior overall survival in DLBCL patients. Based on our results, we conclude that low expression of 14-3-3beta is associated with adverse survival of diffuse large B-cell lymphoma patients, suggesting a novel prognostic marker and potential therapeutic target.